Alat Permainan Edukatif (APE) untuk Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini - Rakhmawati Rakhmawati (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study is to identify and describe educational game tools that can improve the social emotional development of early childhood. This study uses the library research method, which is to collect various kinds of information and data with the help of existing materials in the library such as books, journals/articles, and other sources, as well as relevant previous research results, to obtain answers and theoretical foundations on the issues raised. will be researched. Analysis of the data using content analysis. Based on the research that has been done, it can be seen that from several types of Educational Game Tools (APE) that can be used, such as Lego, puzzles, blocks and finger puppets or hand puppets can improve social emotional development in early childhood.